How negative parenting might hamper identity development: spontaneous aggressiveness and personal belief in a just world. Issue 2 (17th February 2020) - Hofer, Jan; Spengler, Benedikt
ABSTRACT: Based on studies indicating that identity formation is shaped by perceived negative parenting and personal factors, we hypothesized that negative parenting relates to adolescents' self-reported spontaneous aggressiveness and their personal belief in a just world and consequently, is associated with problems developing a firm meaningful interpersonal identity. In a series of four studies, we gathered data from 807 German students aged between 13 and 18 years by using two well-validated methods for measuring of identity development (i.e., Extended Objective Measure of Ego Identity Status, Study 1; Utrecht-Management of Identity Commitments Scale, Studies 2/4). Analyses revealed an indirect link of negative parenting on facets of identity development via spontaneous aggressiveness (Studies 1 and 2). Based on findings that negative parenting was associated with spontaneous aggressiveness via personal belief in a just world (Study 3), analyses conducted in Study 4 indicate a two-staged indirect link of negative parenting on facets of identity development through personal belief in a just world and spontaneous aggressiveness. Above all, problems in the development of and satisfaction with personal meaningful identity commitments could be verified. Implications for research on interpersonal identity formation are discussed.